Studi Evaluasi Pengerukan Sedimen Pada Central Sediment Sump di Lokasi Penambangan Emas PT. Bumi Suksesindo Kabupaten Banyuwangi - Cunanda, Yana; Asmaranto, Runi; Wicaksono, Prima Hadi (Fakultas Teknik, Universitas Brawijaya, 2021)
Central Sediment Sump is the largest sedimentation pond in the gold mine of PT. Bumi Suksesindo. Central Sediment Sump accommodates sediment from region Central Waste Dump (CWD), Pit E, and Pit B West. There is an increases in ore production began in 2018 makes the mining rate up to 8,1 million tons/year. This result increased sediment rates that are accommodated by Central Sediment Sump. The evaluation in this study is based on the amount of dredged sediment volume during 2018 with the volume of sediment that has been accommodated in the Central Sediment Sump. The volume of sediment that came from erosion in the Central Sediment Sump catchment area will be accommodated in the Central Sediment Sump. Dredged sediment volume depends on the bucket size excavators, excavator cycle times, and excavator work times. Excavator work time concern with the time needed to move the sediment volume that is already determined. The results evaluation of dredging sediment will describe sufficient whether or not sediment dredging in 2018 to dredge the sediment accommodated in Central Sediment Sump. Based on the results of this study the volume of sediment accommodates in Central Sediment Sump is 2.004.551,730 m3. Dredged sediment volume during 2018 is 11.755,310 m3. Therefore dredging sediment in 2018 insufficient to dredge all the sediment accommodates in Central Sediment Sump.Â Central Sediment Sump merupakan kolam pengendapan sedimen terbesar di Penambangan EmasÂ PT. Bumi Suksesindo. Central Sediment Sump menampung sedimen dari kawasan Central Waste Dump (CWD), Pit E, dan Pit B West. Adanya peningkatan produksi bijih mulai tahun 2018 menjadikan laju penambangan hingga 8,1 juta ton/tahun. Peningkatan ini mengakibatkan meningkatnya laju sedimen yang ditampung Central Sediment Sump. Evaluasi yang dilakukan pada studi ini berdasarkan pada jumlah volume sedimen terkerukÂ selama tahun 2018 terhadap volume sedimen yang tertangkap di Central Sediment Sump. Volume sedimen yang berasal dari hasil erosi di daerah tangkapan air Central Sediment Sump akan tertangkap di Central Sediment Sump. Volume sedimen terkeruk tergantung pada ukuran bucket excavator, waktu siklus excavator, dan waktu kerja excavator. Waktu kerja excavator menggambarkan waktu yang diperlukan untuk memindahkan volume sedimen yang sudah ditentukan. Hasil evaluasi pengerukan sedimen akan menggambarkan cukup atau tidaknya pengerukan sedimen tahun 2018 untuk mengeruk sedimen yang tertangkap di Central Sediment Sump. Berdasarkan hasil studi ini diperoleh volume sedimen yang tertangkap di Central Sediment Sump sebesar 2.004.551,730 m3. Volume sedimen terkeruk selama tahun 2018 sebesar 11.755,310 m3. Sehingga pengerukan sedimen tahun 2018 tidak mencukupi untuk mengeruk seluruh volume sedimen yang tertangkap di Central Sediment Sump.